(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2022)
This paper is an exploration of my experience of multilingualism in light of existential philosophy and therapeutic practice. As I attempt to bring together several strands of language use and theory, my hope is to create meaning for myself and to encourage others to open up phenomenologically to their own relationship with the world through speech and language.